Effect of Motivation, Communication and Consumer Behavior on Employee Performance at PT. Bank Sumut - Dame Persadanta Tarigan; Gabriel Leonardo Simanjuntak; Davit Gonzales Sembiring; Roni Saputra Waruwu; Deni Faisal Mirza (Journal Research of Social Science, Economics, and Management, 2022)
The background taken by the author in writing research related to the influence of motivation, communication and consumer behavior on employee performance at PT. Bank of North Sumatra. Where the independent variable in thesis writing has problems with the company, therefore the author takes this title and conducts tests and analyzes how high or low the independent variable is on the dependent variable. The research approach used by the author is quantitative research and the type of quantitative descriptive research and the nature of the research used is explanatory research. Then the data processing uses the classical assumption test, then uses multiple linear regression analysis and the final part is hypothesis testing. The conclusions obtained by the authors simultaneously and partially motivational variables (X1), communication (X2), and consumer behavior (X3) have a positive and significant effect on employee performance in the pandemic era at PT. Bank of North Sumatra with a coefficient of determination of 26%, which means that the independent variable is able to improve employee performance in the pandemic era.